Clinical Profile of Snakebite: A Cross-sectional Study In A Upazila (Subdistrict) Health Complex, Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background:Snakebite remains a significant public health concern in many regions of Bangladesh, particularly in southern Chattogram. The Non communicable Disease Control (NCDC) program under DGHS has put tremendous efforts and motivation toward the healthcare provider at Upazilla level to treat cases of snakebite successfully. This study provides a comprehensive analysis of snakebite cases, focusing on the epidemiological patterns, clinical profiles and management observed at Lohagara Upazilla Health Complex.Method: Through a cross-sectional study, analysis of the records of past two years of admitted patients was done which elucidates the demographic characteristics, clinical presentations, and management outcomes of snakebite envenoming in the southern Chattogram community.Result: A total of 202 cases of snakebite were treated successfully, among which 63.9% were male (n=129) and 36.1% were female (n=73). The mean age was approximately 32 years (±17.40) and most were in the age group of 11-20 years (52, 25.74%). 26 (13%) cases developed local envenoming by green-pit viper bite, whereas 6 (2.9%) developed systemic envenoming with neurotoxicity alone and only 1 (0.5%) had features of both neurotoxicity and local swelling. The majority of cases had a short hospital stay, with 171 (84.7%) cases discharged after one day. Maximum patients (55.5%) reached the hospital within one hour of bite. In 53.46% of cases, the species of snakes could not be identified.Conclusion: These findings indicate the need for targeted public health interventions focusing on education and first-aid training, as well as improved pre-hospital care practices to better address snakebite incidents.J Bangladesh Coll Phys Surg 2024; 42: 305-311